Reflections on Divine Violence: Forum on the Actuality of Benjamin’s ‘Critique of Violence’ at Its Centenary, Part III - Melany Cruz; Kaveh Ghoreishi; Sara Minelli (Contexto Internacional, 2023)
Abstract Walter Benjamin published his influential essay ‘Critique of Violence’/‘Zur Kritik der Gewalt’ in 1921, and the work has troubled and provoked thinkers across disciplines for over a century now. This Forum gathers a group of scholars in philosophy, political science, international relations and legal studies to reflect on the actuality of Benjamin’s essay for contemporary critical theory. Melany Cruz, Kaveh Ghoreishi and Sara Minelli engage Benjamin on ‘divine violence.’ As Cruz notes, lynching in contemporary Mexico has become a recurrent phenomenon in nota roja outlets. Due to its brutality, perceptions of lynching have been reduced to a form of uncivilised and irrational crime. In opposition to this perspective, Cruz theorises the political dimension of the violence of lynching by drawing from Benjamin and argues that such violence symbolically and affectively dramatises the suspension of ‘mere life’ in which the communities enacting the lynchings are immersed in the current conditions of neoliberal Mexico. In this way, it is possible to claim that lynching, in Benjamin’s terms, constitutes a form of divine violence that has the capacity to reveal and communicate the need to end the fear- and anger-provoking condition of ‘mere life.’ In the second section, Ghoreishi and Minelli propose a reading of ‘divine’ as opposed to ‘mythical violence’ that brings out the radical elements of some contemporary struggles by interpreting some examples of strike which took place in Iranian Kurdistan (Rojhilat) in the last forty years. They understand the revolutionary ‘general strike’ considered by Benjamin as what Jesi has called a ‘suspension of time,’ bringing ‘normal’ economic and social relations to a halt. In this sense, the general strikes in Kurdistan can be said to bring the mythological temporality of oppression to an end. These struggles, in which new forms of collectivity have emerged and been experimented, should, therefore, be seen as anticipations of the ‘divine violence’ that puts an end to ‘mythical violence.’